Experimental Investigation of Damping Enhancement and Low Cycle Fatigue Characteristics of CNT-Reinforced Hybrid Polymer Composite Curved Beam Structure - Nouby M. Ghazaly, S.Devendiran, S. Mageshwaran, Madhusan sivakumar, Ashwin.S (International Journal of Advanced Science and Technology, 2019)
This research discusses the influence of the weight percentage of carbon nanotubes (CNT) in the curved composite beam structure through vibration testing. GFRP composite curved structured beams are fabricated with weight percentages 1, 2, 3, 4 and 5 wt. % of CNT with support of vacuum helped hand layup system. Structural vibration response of the CNT reinforced curved composite beam are studied in terms of natural frequencies and damping ratio. The natural frequencies and damping ratio of the curved composite beams are determined. It is observed that the higher values of natural frequencies are obtained at the 3 wt. % CNT-GFRP hybrid composite curved beam. Its value increases 44.31% and 36.26% higher than that of GFRP composite beams under clamped-clamped condition and clamped-free boundary conditions, respectively. Also, the increase in the damping factor is observed concerning the weight percentage of the CNT. The forced vibration analysis is performed with (3 wt. %) and without CNT and it is observed that the fundamental natural frequency of 3% CNT-GFRP composite curved beam decreased by 12.6% and 6.6%, under the condition of low cycle fatigue experimentation of 12500 cycles.